The Evaluation of a three-phase uncontrolled full-wave rectifier driven by a three-phase AC generator - Didik Sukoco; Rama Arya Sobhita; Anggara Trisna Nugraha; Abdullah Waasi' (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2026)
The rapid evolution of technology is significantly transforming various industries, with electrical engineering being one of the most impacted fields. As access to information continues to expand, advancements in science and technology are accelerating, necessitating the optimization of existing knowledge for future applications. In electrical engineering, refining both theoretical concepts and practical implementations is essential to enhancing the efficiency and performance of power systems, particularly in industrial settings where electricity demand is substantial. One key approach to achieving this optimization is through the study and analysis of a three-phase uncontrolled full-wave rectifier circuit powered by a three-phase AC generator. This paper presents a comprehensive examination of this system, focusing on improving its performance and efficiency for industrial applications. A deeper understanding of the theoretical principles and practical challenges associated with this rectifier circuit will contribute to the development of more effective and sustainable power conversion systems.